Melt-mixing extrusion method and melt-mixing extrusion apparatus

JP2026166404APending Publication Date: 2026-10-14DAIO PAPER CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059314
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、溶融混練押出装置の押出口から吐出される材料を好適に切断できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166404000001_ABST
    Figure 2026166404000001_ABST
Patent Text Reader

Abstract

The material discharged from the extrusion port of the melt-mixing extruder can be cut appropriately. [Solution] The method includes a melt-kneading extrusion step in which a material containing resin and fibrous cellulose is melted and kneaded in a melt-kneading extruder and discharged from an extrusion port, and a cutting step in which the melted and kneaded material discharged from the extrusion port is cut with a cutting blade, and a cooling step in which cooling water is projected onto at least one of the discharged material and the cutting blade.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a melt-kneading extrusion method and a melt-kneading extrusion apparatus. [Background technology]

[0002] In recent years, fine cellulose fibers such as cellulose nanofibers and microfiber cellulose (microfibrillated cellulose) have attracted attention for their use as reinforcing materials in resins, and many proposals have been made for their application.

[0003] To obtain this type of composite resin, a material containing resin and fine fibrous cellulose (hereinafter also simply referred to as "fibrous cellulose") is melted and kneaded with the resin using a melt-kneading extruder to produce resin pellets.

[0004] Patent Document 1 proposes a kneading extruder equipped with a cutting mechanism and a cooling and conveying mechanism for the material extruded from the extrusion port. The cooling and conveying mechanism receives the material that has been cut and fallen from the extrusion port, and a guide section is provided in which a liquid for cooling the material is introduced to convey the material by the flow of the liquid.

[0005] This Patent Document 1 describes a system in which a certain amount of time is required for the resin material discharged from a melt-mixing extruder to cool down. Therefore, to solve the problem that the resin material discharged from the extruder may deteriorate due to the heat accumulated during melting and heating, the material is cut and falls from the extruder port, and then cooled by the cooling and conveying mechanism. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Japanese Patent Publication No. 2024-118213 [Overview of the project] [Problems that the invention aims to solve]

[0007] On the other hand, cutting the material extruded from the extrusion port into short chips is desirable from the standpoint of ensuring good handling later on.

[0008] However, the inventors have found that composite resin materials of resin and fibrous cellulose are difficult to cut properly with a cutting blade because the extruded material is at a considerably high temperature due to heat storage and exhibits adhesiveness.

[0009] Therefore, the main object of the present invention is to provide a melt-kneading extrusion method and a melt-kneading extrusion apparatus that can suitably cut the material discharged from the extrusion port of the melt-kneading extrusion apparatus. [Means for solving the problem]

[0010] The embodiments of the present invention for solving the above technical problems are as follows. (First aspect) A melt-kneading extrusion step in which a material containing resin and fibrous cellulose is melted and kneaded in a melt-kneading extruder and discharged from an extrusion port, The process includes a cutting step of cutting the molten and kneaded material discharged from the extrusion port with a cutting blade, The cooling step includes projecting cooling water onto at least one of the discharged material and the cutting blade, A melt-kneading extrusion method characterized by the following: (Second aspect) A melt-kneading extruder that melts and kneads a material containing resin and fibrous cellulose and discharges it from an extrusion port, The device includes a cutting blade for cutting the molten and kneaded material discharged from the extrusion port, The cooling means includes a means for projecting cooling water onto at least one of the discharged material and the cutting blade, A melt-kneading extrusion apparatus characterized by the following features. [Effects of the Invention]

[0011] According to the present invention, the material discharged from the discharge port of a melt-kneading extrusion apparatus can be suitably cut. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] [Figure 1] It is a schematic diagram of a twin-screw melt-kneading extrusion apparatus according to an embodiment. [Figure 2] It is a partially broken partial schematic diagram of the tip portion including the extrusion section. [Figure 3] It is a schematic diagram of the extrusion section. [Figure 4] It is a schematic explanatory view (a view taken along line 4-4 in FIG. 1 as viewed in the direction of the arrow) of the cutting device and the cooling means located at the outlet of the extrusion section, as viewed from the left to the right in FIG. 1. [Figure 5] It is a cross-sectional view of the extrusion apparatus and the screw. [Figure 6] It is a side view of the screw. [Figure 7] It is a view of the discharge port as viewed from its front side. [Figure 8] It is an explanatory diagram of a defective cutting example. MODES FOR CARRYING OUT THE INVENTION

[0013] Hereinafter, preferred embodiments of the present invention will be described. Note that the content of the present invention should be interpreted based on the matters stated in the claims, and should not be interpreted as being limited to the embodiments.

[0014] (Outline Description of the Embodiment of the Present Invention) The present invention aims to obtain a composite resin made of a material containing a resin and fibrous cellulose.

[0015] In the embodiment of the present invention, in order to obtain the composite resin, a cutting step of cutting the melted and kneaded material discharged from the discharge port with a cutting blade is performed on a melt-kneading extruder that melts and kneads a material containing a resin and fibrous cellulose and discharges the material from the discharge port.

[0016] However, as mentioned above, the material extruded from the extrusion port is at a considerably high temperature due to heat accumulation and exhibits stickiness, making it difficult to perform proper cutting with a cutting blade. As a result, cutting defects may occur.

[0017] An example of such a cutting defect is shown in Figure 8. In this example of a cutting defect, adjacent chips S1, S1 stick together due to their adhesive properties upon cutting, and fall off as a bonded mass. The inventors have found that this type of cutting defect can occur in various forms. For example, a dozen or so chips may come into contact with each other in a direction perpendicular to the length (discharge) direction, resulting in a large area resembling a cushion sheet with uneven surfaces on both sides.

[0018] Furthermore, if extruded material or chips adhere to the cutting blade, and the blade attempts to cut the subsequent extruded material in this adhered state, the cutting failure by the cutting blade becomes even more severe.

[0019] In embodiments of the present invention, a cooling step is included in which cooling water is projected onto at least one of the extruded material and the cutting blade, thereby enabling suitable cutting of the material extruded from the extrusion port of the melt-kneading extruder. Therefore, this includes both configurations in which cooling water is projected onto both the discharged material and the cutting blade, and configurations in which cooling water is projected onto only one of the discharged material or the cutting blade. In the following explanation, we will first describe an example of the production of a material containing resin and fibrous cellulose supplied to a melt-kneading extruder to obtain a composite resin. Following that, we will describe the melt-kneading extruder and the cooling means.

[0020] (Regarding fibrous cellulose) When obtaining composite resins, since resins are generally hydrophobic while fibrous cellulose is hydrophilic, in order to use fibrous cellulose as a reinforcing material for resins, it is necessary to ensure good dispersibility of the fibrous cellulose when dispersing it in the resin.

[0021] To improve dispersibility, a method of modifying fine fibrous cellulose by substituting hydroxyl groups with carbamate groups has been proposed, and its effectiveness has been demonstrated.

[0022] The fibrous cellulose composite resin in this embodiment contains fibrous cellulose and a resin, and preferably further contains an acid-modified resin. When an acid-modified resin is included, some or all of the carbamate groups are ionically bonded with the acid groups of the acid-modified resin. This ionic bonding improves the reinforcing effect of the resin.

[0023] The fibrous cellulose according to the present invention is preferably fine fiber. It is more preferably microfiber cellulose (microfibrillated cellulose) with an average fiber diameter of 0.1 μm or more. When it is microfiber cellulose, the reinforcing effect of the resin is significantly improved. Furthermore, microfiber cellulose is easier to modify with carbamate groups (carbamate) than cellulose nanofibers, which are also fine fibers.

[0024] The microfiber cellulose according to the present invention refers to fibers with a wider average fiber width than cellulose nanofibers. Specifically, the average fiber diameter is, for example, 0.1 to 20 μm, preferably 0.2 to 19 μm, and more preferably more than 0.5 μm and 18 μm or less. If the average fiber diameter of microfiber cellulose falls below 0.1 μm, it becomes indistinguishable from cellulose nanofiber, and the effect of improving the strength (especially the flexural modulus) of the resin may not be sufficiently obtained. In addition, the defibrillation time will be longer, requiring a large amount of energy.

[0025] Furthermore, the dewatering properties of the microfiber cellulose slurry deteriorate. Poor dewatering properties require a large amount of energy for drying, and applying a large amount of energy to drying can cause thermal degradation of the microfiber cellulose, potentially reducing its strength. On the other hand, if the average fiber diameter of the microfiber cellulose exceeds 20 μm, the reinforcing effect may become insufficient.

[0026] The fibrous cellulose containing microfiber cellulose according to the present invention can be obtained by defibrating (finely pulping) a cellulose raw material (hereinafter also referred to as "raw material pulp"). As the raw material pulp, one or more types can be selected and used from, for example, wood pulp made from hardwoods, softwoods, etc., non-wood pulp made from straw, bagasse, cotton, hemp, pulp fibers, etc., recycled paper pulp (DIP) made from recycled waste paper, waste paper, etc., etc. The above-mentioned cellulose raw materials may also be in the form of crushed material (powdered material), such as cellulose powder.

[0027] However, in order to avoid the inclusion of impurities as much as possible, it is preferable to use wood pulp as the raw material pulp. As for wood pulp, one or more types can be selected and used from chemical pulps such as hardwood kraft pulp (LKP) and softwood kraft pulp (NKP), and mechanical pulp (TMP), etc.

[0028] The raw pulp can be pretreated by chemical methods prior to defibration. Examples of chemical pretreatments include hydrolysis of polysaccharides with acid (acid treatment), hydrolysis of polysaccharides with enzymes (enzyme treatment), swelling of polysaccharides with alkali (alkali treatment), oxidation of polysaccharides with an oxidizing agent (oxidation treatment), and reduction of polysaccharides with a reducing agent (reduction treatment). However, as a chemical pretreatment, enzymatic treatment is preferred, and it is more preferable to also apply one or more treatments selected from acid treatment, alkali treatment, and oxidation treatment.

[0029] For enzymatic treatment, it is preferable to use at least one of cellulase-type enzymes and hemicellulase-type enzymes, and more preferably both in combination. Using these enzymes makes defibration of cellulose raw materials easier. Cellulase-type enzymes induce the decomposition of cellulose in the presence of water. Hemicellulase-type enzymes induce the decomposition of hemicellulose in the presence of water.

[0030] The amount of enzyme added to the cellulose raw material is determined by factors such as the type of enzyme, the type of wood used as the raw material (coniferous or hardwood), and the type of mechanical pulp. However, the amount of enzyme added to the cellulose raw material is preferably 0.1 to 3% by mass, more preferably 0.3 to 2.5% by mass, and particularly preferably 0.5 to 2% by mass. If the amount of enzyme added is less than 0.1% by mass, the effect of the enzyme addition may not be sufficiently obtained. On the other hand, if the amount of enzyme added exceeds 3% by mass, the cellulose may be saccharified, and the yield of fine fibers may decrease. There is also the problem that the improvement in effect may not be commensurate with the increase in the amount of enzyme added.

[0031] When using a cellulase-type enzyme, the pH during enzyme treatment is preferably in the weakly acidic range (pH=3.0~6.9) from the viewpoint of the reactivity of the enzymatic reaction. On the other hand, when using a hemicellulase-type enzyme, the pH during enzyme treatment is preferably in the weakly alkaline range (pH=7.1~10.0).

[0032] After enzyme treatment, it is preferable to deactivate the enzyme. Methods for deactivating the enzyme include, for example, adding an alkaline aqueous solution (preferably pH 10 or higher, more preferably pH 11 or higher) or adding hot water at 80-100°C.

[0033] Enzyme treatment, acid treatment, or oxidation treatment prior to defibration can lower the water retention of fibrous cellulose, increase its crystallinity, and improve its homogeneity. In this respect, lower water retention of fibrous cellulose makes it easier to dehydrate, thus improving the dewatering properties of the fibrous cellulose slurry.

[0034] Enzymatic, acidic, or oxidative treatment of raw pulp breaks down the amorphous regions of hemicellulose and cellulose in the pulp. As a result, the energy required for defibration can be reduced, improving the uniformity and dispersibility of fibrous cellulose. However, since pretreatment reduces the aspect ratio of fibrous cellulose, it is preferable to avoid excessive pretreatment when using it as a reinforcing material for resins.

[0035] The defibration of raw pulp can be carried out by beating it using, for example, a homogenizer such as a beater, high-pressure homogenizer, or high-pressure homogenization device; a millstone-type friction machine such as a grinder or crusher; a single-screw kneader; a multi-screw kneader; a kneader refiner; or a jet mill. However, it is preferable to use a refiner or a jet mill.

[0036] The average fiber length (average length of a single fiber) of fibrous cellulose is preferably 0.10 to 2.00 mm, more preferably 0.12 to 1.50 mm, and particularly preferably 0.15 to 1.00 mm. If the average fiber length is less than 0.10 mm, a three-dimensional network of fibers cannot be formed, which may reduce the flexural modulus of the composite resin, and even if homogeneity is improved by increasing the fineness ratio to more than 35%, the reinforcing effect may not be improved. On the other hand, if the average fiber length exceeds 2.00 mm, the reinforcing effect may be insufficient. The average fiber length of fibrous cellulose can be arbitrarily adjusted, for example, by selecting raw pulp, pre-treatment, defibration, etc.

[0037] In this specification, "fine ratio" refers to the mass-based proportion of pulp fibers with a fiber length of 0.2 mm or less.

[0038] The fineness ratio of fibrous cellulose is preferably 10% or more and 55% or less, more preferably 20-50%, and particularly preferably 30-45%. When the fineness ratio is 10% or more, a certain proportion of homogeneous fibers is ensured, and the homogeneity of the composite resin is ensured. As a result, the flexural modulus is ensured. When the fine fiber content exceeds 55%, the fluidity of the composite resin decreases. This decrease in fluidity can lead to a reduction in the homogeneity of the composite resin, potentially resulting in insufficient reinforcement. In contrast, if the fine fiber content is 55% or less, the composite resin maintains high fluidity, and it has been found that it can be extruded using a melt-mixing extruder even when the fiber content is 55% or higher.

[0039] It is also preferable to keep the fineness ratio of the cellulose raw material used to make fibrous cellulose within a predetermined range. Specifically, it is preferable that the fineness ratio of the cellulose raw material used to make fibrous cellulose be 1% or more, more preferably 3-20%, and particularly preferable 5-18%. If the fineness ratio of the cellulose raw material before defibration is within the above range, it is thought that there will be less damage to the fibers after defibration, and the reinforcing effect of the resin will be improved.

[0040] The fineness ratio can be adjusted by pretreatment such as enzymatic treatment. When enzymatic treatment is performed, the fibers themselves may become brittle, potentially reducing the reinforcing effect of the resin. Therefore, from this perspective, the amount of enzyme added is preferably 2% by mass or less, more preferably 1% by mass or less, and particularly preferably 0.5% by mass or less. Alternatively, the material may be in a form without enzymatic treatment (amount added: 0% by mass).

[0041] The aspect ratio of the fibrous cellulose is preferably 2 to 15,000, more preferably 10 to 10,000. If the aspect ratio is less than 2, a three-dimensional network cannot be sufficiently constructed, and even if the average fiber length is 0.10 mm or more, the reinforcing effect may be insufficient. On the other hand, if the aspect ratio exceeds 15,000, the entanglement of the fibrous cellulose becomes high, and dispersion in the resin may be insufficient.

[0042] In this specification, "fibrillation rate" refers to the value obtained by dissociating fibrous cellulose in accordance with JIS-P-8220:2012 "Pulp - Dissociation Method" and measuring the resulting dissociated pulp using FiberLab. (Kajaani).

[0043] The fibrillation rate of fibrous cellulose is preferably 1.0 to 30.0%, more preferably 1.5 to 20.0%, and particularly preferably 2.0 to 15.0%. If the fibrillation rate exceeds 30.0%, the contact area with water becomes too large, and even if defibration is performed within the range where the average fiber width remains 0.1 μm or more, dehydration may become difficult. On the other hand, if the fibrillation rate falls below 1.0%, there are few hydrogen bonds between fibrils, and it may not be possible to form a strong three-dimensional network.

[0044] The crystallinity of the fibrous cellulose is preferably 50% or higher, more preferably 55% or higher, and particularly preferably 60% or higher. If the crystallinity falls below 50%, although the miscibility with pulp and cellulose nanofibers improves, the strength of the fibers themselves decreases, which may prevent the improvement of the resin's strength. On the other hand, the degree of crystallinity of fibrous cellulose is preferably 95% or less, more preferably 90% or less, and particularly preferably 85% or less. If the degree of crystallinity exceeds 95%, the proportion of strong hydrogen bonds within the molecule increases, the fibers themselves become rigid, and the dispersibility deteriorates. The degree of crystallinity of fibrous cellulose can be arbitrarily adjusted, for example, by selecting the raw pulp, pre-treatment, and micronization process.

[0045] As previously mentioned, it is preferable to use fibrous cellulose that has carbamate groups. There are no particular limitations on how the carbamate groups are obtained. For example, the cellulose raw material may have carbamate groups because it has been carbamateized, or the fibrous cellulose (finely ground cellulose raw material) may have carbamate groups because it has been carbamateized.

[0046] Here, having a carbamate group means that a carbamate group (an ester of carbamic acid) has been introduced into the fibrous cellulose. The carbamate group is a group represented by -O-CO-NH-, for example, -O-CO-NH2, -O-CONHR, -O-CO-NR2, etc. In other words, the carbamate group can be represented by the following structural formula (1).

[0047] [ka]

[0048] Here, R1 and R2 are independently at least one of a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group, and a derivative thereof.

[0049] In fibrous cellulose containing carbamate groups (introduced with carbamate groups), some or all of the highly polar hydroxyl groups are replaced with relatively less polar carbamate groups. Therefore, fibrous cellulose containing carbamate groups has low hydrophilicity and high affinity for low-polarity resins. As a result, fibrous cellulose containing carbamate groups exhibits excellent uniform dispersibility with resins. Furthermore, fibrous cellulose slurry containing carbamate groups has low viscosity and good handling properties.

[0050] Regarding the introduction of carbamate groups into fibrous cellulose (or cellulose raw material if carbamateization is performed before defibration), as mentioned above, there are two methods: one in which the cellulose raw material is carbamateized first and then refined, and another in which the cellulose raw material is refined first and then carbamateized. The order of refinement (e.g., defibration) and carbamateization is not limited. However, it is preferable to perform carbamateization first, followed by defibration. This is because the cellulose raw material has high dehydration efficiency before defibration, and the heating associated with carbamateization makes the cellulose raw material more easily defibrated.

[0051] Fibrous cellulose is dispersed in an aqueous medium to form a dispersion (slurry) as needed. While it is particularly preferable that the aqueous medium is entirely water, an aqueous medium containing a portion of another liquid that is compatible with water can also be used. Other liquids that can be used include lower alcohols with 3 or fewer carbon atoms.

[0052] The solid content concentration of the slurry is preferably 2 to 10% by mass, more preferably 3 to 8% by mass. If the solid content concentration is less than 2% by mass, excessive energy may be required during dehydration and drying. On the other hand, if the solid content concentration exceeds 10% by mass, the fluidity of the slurry itself decreases, and uniform mixing may not be possible even when using a dispersant. In this regard, for example, if the fineness ratio exceeds 35%, the upper limit for slurry solid content concentration from the standpoint of ensuring fluidity is 4.0% by mass. In contrast, if the fineness ratio is 35% or less, the upper limit is 10% (preferably 6.0% by mass), as described above. Therefore, if the fineness ratio is 35% or less and the slurry solid content concentration is 10% by mass or less, it is possible to reduce the amount of aqueous medium that needs to be removed from the slurry, and the solid content concentration can be increased, which has advantages such as reducing costs.

[0053] (Acid-modified resin) When fibrous cellulose is impregnated with an acid-modified resin, the acid groups ionically bond with some or all of the carbamate groups, as described above. This ionic bonding improves the reinforcing effect of the resin.

[0054] Examples of acid-modified resins that can be used include acid-modified polyolefin resins, acid-modified epoxy resins, and acid-modified styrene-based elastomer resins. However, it is preferable to use acid-modified polyolefin resins. Acid-modified polyolefin resins are copolymers of an unsaturated carboxylic acid component and a polyolefin component.

[0055] As the polyolefin component, one or more polymers of alkenes such as ethylene, propylene, butadiene, and isoprene can be selected and used. However, it is preferable to use polypropylene resin, which is a polymer of propylene.

[0056] As the unsaturated carboxylic acid component, one or more can be selected from, for example, maleic anhydrides, phthalic anhydrides, itaconic anhydrides, citraconic anhydrides, citric anhydrides, etc. However, maleic anhydrides are preferably used. In other words, it is preferable to use maleic anhydride-modified polypropylene resin.

[0057] The amount of acid-modified resin to be mixed is preferably 0.1 to 1,000 parts by mass, more preferably 1 to 500 parts by mass, and particularly preferably 10 to 200 parts by mass, per 100 parts by mass of fibrous cellulose. In particular, when the acid-modified resin is maleic anhydride-modified polypropylene resin, the amount is preferably 1 to 200 parts by mass, and more preferably 10 to 100 parts by mass. If the amount of acid-modified resin mixed is less than 0.1 parts by mass, the improvement in strength is insufficient. On the other hand, if the amount of resin mixed exceeds 1,000 parts by mass, it becomes excessive and tends to decrease the strength.

[0058] The weight-average molecular weight of maleic anhydride-modified polypropylene is, for example, 1,000 to 100,000, preferably 3,000 to 50,000.

[0059] Furthermore, the acid value of maleic anhydride-modified polypropylene (titrated with potassium hydroxide in accordance with JIS-K2501) is preferably 0.5 mg KOH / g or more and 100 mg KOH / g or less, and more preferably 1 mg KOH / g or more and 50 mg KOH / g or less.

[0060] Furthermore, the MFR (melt flow rate) of the acid-modified resin is preferably 2000 g / 10 min or less (measured under conditions of 190°C / 2.16 kg in accordance with JIS-K7210), more preferably 1500 g / 10 min or less, and particularly preferably 500 g / 10 min. If the MFR exceeds 2000 g / 10 min, the dispersibility of the fibrous cellulose may decrease.

[0061] (Dispersant) Cellulose raw materials or fibrous cellulose can be mixed with a dispersant. Preferred dispersants are compounds having an amine group and / or a hydroxyl group in aromatic compounds, and compounds having an amine group and / or a hydroxyl group in aliphatic compounds.

[0062] Dispersants inhibit hydrogen bonding between fibrous cellulose fibers. Therefore, during the kneading of fibrous cellulose and resin, the fibrous cellulose is reliably dispersed within the resin. Furthermore, dispersants also play a role in improving the compatibility between fibrous cellulose and resin. In this respect, the dispersibility of fibrous cellulose within the resin is improved.

[0063] While it is possible to add a phase solvent (chemical) separately during the kneading of fibrous cellulose and resin, mixing the fibrous cellulose and dispersant (chemical) beforehand results in more uniform adhesion of the chemical to the fibrous cellulose, thereby improving compatibility with the resin.

[0064] For example, the mixing of fibrous cellulose and resin is carried out at a temperature above the melting point of the resin. However, if the resin is polypropylene, for example, its melting point is 160°C, and therefore the mixing of fibrous cellulose and resin is carried out at around 180°C. However, if a dispersant (liquid) is added at this high temperature, it will dry out instantly. Therefore, one method involves using a resin with a low melting point to create a masterbatch (a composite resin with a high concentration of cellulose fibers), and then lowering the concentration with a regular resin. However, resins with low melting points generally have low strength. Consequently, this method may reduce the strength of the composite resin.

[0065] The amount of dispersant to be mixed is preferably 0.1 to 1,000 parts by mass, more preferably 1 to 500 parts by mass, and particularly preferably 10 to 200 parts by mass, per 100 parts by mass of fibrous cellulose. If the amount of dispersant mixed is less than 0.1 parts by mass, the improvement in resin strength may not be sufficient. On the other hand, if the amount of dispersant mixed exceeds 1,000 parts by mass, it becomes excessive and tends to decrease the resin strength.

[0066] The aforementioned acid-modified resin improves compatibility through ionic bonding between the acid groups and the carbamate groups of fibrous cellulose, thereby enhancing its reinforcing effect. Its large molecular weight makes it easily compatible with resins, which is thought to contribute to improved strength. On the other hand, the above-mentioned dispersant intervenes between the hydroxyl groups of fibrous cellulose to prevent aggregation, thereby improving dispersibility in the resin. Furthermore, because its molecular weight is smaller than that of the acid-modified resin, it can enter the narrow spaces between fibrous cellulose where the acid-modified resin cannot penetrate, thus improving dispersibility and enhancing strength. From this perspective, the molecular weight of the acid-modified resin is preferably 2 to 2,000 times, more preferably 5 to 1,000 times, the molecular weight of the dispersant.

[0067] To explain in more detail, resin powder (or granules) physically interposes itself between fibrous cellulose fibers, inhibiting hydrogen bonding and thereby improving the dispersibility of the fibrous cellulose. In contrast, acid-modified resin improves compatibility by ionic bonding between the acid groups and the carbamate groups of the fibrous cellulose, thereby enhancing the reinforcing effect. In this respect, both dispersants inhibit hydrogen bonding between fibrous cellulose fibers, but because resin powder is on the micro-order, it physically intervenes and suppresses hydrogen bonding. Therefore, although its dispersibility is lower than that of dispersants, the resin powder itself melts and forms a matrix, so it does not contribute to a decrease in physical properties. On the other hand, dispersants are at the molecular level and are extremely small, so they effectively inhibit hydrogen bonding by covering the fibrous cellulose and improving the dispersibility of the fibrous cellulose. However, they may remain in the resin and contribute to a decrease in physical properties.

[0068] (Example of manufacturing method) A mixture of fibrous cellulose, acid-modified resin, and dispersant can be dried and pulverized into a powder before being kneaded with the resin. This form eliminates the need to dry the fibrous cellulose separately before kneading with the resin, resulting in better thermal efficiency. Furthermore, if a dispersant is mixed into the mixture, there is a low risk that the fibrous cellulose (e.g., microfiber cellulose) will not redisperse even after the mixture is dried.

[0069] The mixture may be dehydrated before drying, if necessary. This dehydration can be carried out by selecting one or more types of dehydration equipment from among, for example, a belt press, screw press, filter press, twin roll, twin wire former, valveless filter, center disc filter, membrane processing, and centrifuge. From the viewpoint of dewatering efficiency and economics, a screw press is particularly preferred.

[0070] The drying of the mixture can be carried out by selecting one or more of the following methods: rotary kiln drying, disc drying, airflow drying, fluidized bed drying, spray drying, drum drying, screw conveyor drying, paddle drying, single-screw kneading drying, multi-screw kneading drying, vacuum drying, agitation drying, etc. In terms of drying efficiency and operational stability, indirect heating rotary dryers (e.g., steam tube dryers: STD) are particularly suitable.

[0071] For example, a mixture (dried material) with a dry content of 10% or less, typically around 3-7%, can be ground into a powder if necessary. Grinding of the dried material can be done by selecting one or more types of mills from, for example, a bead mill, kneader, disper, twist mill, cut mill, hammer mill, etc.

[0072] The average particle size of the powder is preferably 1 to 10,000 μm, more preferably 10 to 5,000 μm, and particularly preferably 100 to 1,000 μm. If the average particle size of the powder exceeds 10,000 μm, it may result in poor kneadability with the resin. On the other hand, reducing the average particle size of the powder to less than 1 μm requires a large amount of energy, making it uneconomical. The average particle size of powdered materials can be controlled not only by controlling the degree of grinding, but also by classification using classification devices such as filters and cyclones.

[0073] The bulk density of the mixture (powder) is preferably 0.03 to 1.0, more preferably 0.04 to 0.9, and particularly preferably 0.05 to 0.8. If the bulk density exceeds 1.0, the hydrogen bonds between the fibrous celluloses become stronger, and dispersion in the resin tends to become more difficult. On the other hand, a bulk density below 0.03 is disadvantageous in terms of transportation costs. The bulk density can be obtained by measuring it in accordance with JIS K7365.

[0074] The moisture content of the mixture (powder) supplied to the melt-kneading extruder is preferably 50% or less, more preferably 30% or less, and particularly preferably 10% or less. If the moisture content exceeds 50%, the energy required for kneading with the resin becomes enormous, making it uneconomical. The moisture content was calculated using the following formula, after the sample was held at 105°C for 6 hours or more in a constant-temperature drying oven and the mass at which no further mass fluctuation was observed was taken as the post-drying mass. Fiber moisture content (%) = [(Mass before drying - Mass after drying) ÷ Mass before drying] × 100 In contrast, the solid content concentration is as follows: Solid content concentration (%) = (mass after drying ÷ mass before drying) × 100 (= 100 - fiber moisture content)

[0075] (Resin mixing process) Prior to dehydration and drying, it is preferable to incorporate a powdered resin through a "resin mixing process." If this is referred to as a pre-resin, the presence of this pre-resin inhibits hydrogen bonding between the dehydrated and dried microfiber cellulose, thereby improving dispersibility in the pre-resin during kneading.

[0076] The pre-resin used here may be the same type as the resin mixed with the fibrous cellulose (the resin used as the main raw material) or a different type, but it is preferable that it be the same type. If the main raw material is, for example, polypropylene resin, the pre-resin can also be polypropylene resin.

[0077] Furthermore, the pre-resin may contain the aforementioned dispersant and / or acid-modified resin. When the acid-modified resin is, for example, a maleic anhydride-modified polypropylene resin in which propylene is the polyolefin component and maleic anhydrides are the unsaturated carboxylic acid components, it is preferably in the form of a powdered maleic anhydride-modified polypropylene resin obtained prior to dehydrating and drying the fibrous cellulose.

[0078] The fibrous cellulose-containing material obtained as described above, for example in powder form, is subjected to a dehydration step and a drying step, and then kneaded in a kneading step to obtain a fibrous cellulose composite resin. This mixing can be carried out, for example, by mixing pelletized resin with powdered fibrous cellulose-containing material, or by first melting the resin and then adding the powdered material to the molten material. Acid-modified resins and dispersants can also be added at the melt-mixing stage, but as mentioned above, it is preferable to add them prior to the dehydration and drying of the fibrous cellulose.

[0079] For the melt-mixing process, one or more types of equipment can be selected and used from, for example, single-screw or multi-screw (two or more) mixing extruders, mixing rolls, kneaders, roll mills, Banbury mixers, screw presses, dispersers, etc. While single-screw and twin-screw extruders are commonly used, twin-screw extruders offer higher productivity and greater operational flexibility compared to single-screw extruders. Therefore, twin-screw extruders are preferred for the production of composite resin composition pellets in the embodiments of the present invention. Two or more twin-screw compounding extruders may be used in parallel or in series.

[0080] The mixing temperature is above the glass transition temperature of the resin and varies depending on the type of resin, but is preferably 80 to 280°C, more preferably 90 to 260°C, and particularly preferably 100 to 240°C.

[0081] As thermoplastic resins to be used, one or more can be selected from, for example, polyolefins such as polypropylene (PP) and polyethylene (PE), polyester resins such as aliphatic polyester resins and aromatic polyester resins, polyacrylic resins such as polystyrene, methacrylate, and acrylate, polyamide resins, polycarbonate resins, and polyacetal resins.

[0082] However, it is preferable to use at least one of polyolefin and polyester resin. Furthermore, as polyolefin, polypropylene is preferred. In addition, as polyester resin, aliphatic polyester resins such as polylactic acid and polycaprolactone can be exemplified, and aromatic polyester resins such as polyethylene terephthalate can be exemplified, but it is preferable to use a biodegradable polyester resin (also simply called "biodegradable resin").

[0083] As for biodegradable resins, one or more can be selected and used from, for example, hydroxycarboxylic acid-based aliphatic polyesters, caprolactone-based aliphatic polyesters, dibasic acid polyesters, etc.

[0084] As the hydroxycarboxylic acid aliphatic polyester, one or more can be selected and used from among homopolymers of hydroxycarboxylic acids such as lactic acid, malic acid, glucose acid, and 3-hydroxybutyric acid, or copolymers using at least one of these hydroxycarboxylic acids. However, it is preferable to use polylactic acid, copolymers of lactic acid and the above hydroxycarboxylic acids excluding lactic acid, polycaprolactone, or copolymers of at least one of the above hydroxycarboxylic acids and caprolactone, and it is particularly preferable to use polylactic acid.

[0085] For example, L-lactic acid or D-lactic acid can be used as the lactic acid, and these lactic acids may be used individually or two or more types may be selected and used together.

[0086] As the caprolactone-based aliphatic polyester, one or more can be selected and used from, for example, a homopolymer of polycaprolactone or a copolymer of polycaprolactone or the above-mentioned hydroxycarboxylic acid.

[0087] As the dibasic acid polyester, one or more types can be selected and used from, for example, polybutylene succinate, polyethylene succinate, and polybutylene adipate.

[0088] Biodegradable resins may be used individually or in combination of two or more types.

[0089] The resin may contain inorganic fillers, preferably in a proportion that does not hinder thermal recycling. Examples of these inorganic fillers include elemental metal elements from Groups I to VIII of the periodic table, such as Fe, Na, K, Cu, Mg, Ca, Zn, Ba, Al, Ti, and silicon, as well as oxides, hydroxides, carbon salts, sulfates, silicates, sulfites, and various clay minerals composed of these compounds.

[0090] Specifically, examples include barium sulfate, calcium sulfate, magnesium sulfate, sodium sulfate, calcium sulfite, zinc oxide, silica, heavy calcium carbonate, light calcium carbonate, aluminum borate, alumina, iron oxide, calcium titanate, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, sodium hydroxide, magnesium carbonate, calcium silicate, clay worlastonite, glass beads, glass powder, silica sand, silica, quartz powder, diatomaceous earth, white carbon, glass fiber, etc. Multiple inorganic fillers may be included. They may also be found in recycled paper pulp.

[0091] The blending ratio of fibrous cellulose and resin is preferably 1 part by mass or more of fibrous cellulose and 99 parts by mass or less of resin, more preferably 2 parts by mass or more of fibrous cellulose and 98 parts by mass or less of resin, and particularly preferably 3 parts by mass or more of fibrous cellulose and 97 parts by mass or less of resin. Also preferably 50 parts by mass or less of fibrous cellulose and 50 parts by mass or more of resin, more preferably 40 parts by mass or less of fibrous cellulose and 60 parts by mass or more of resin, and particularly preferably 30 parts by mass or less of fibrous cellulose and 70 parts by mass or more of resin. In particular, when the amount of fibrous cellulose is 10 to 50 parts by mass, the strength of the resin composition, especially the flexural strength and tensile modulus, can be significantly improved.

[0092] The proportions of fibrous cellulose and resin in the final resin composition are typically the same as the above-mentioned proportions of fibrous cellulose and resin.

[0093] Dissolution parameters (cal / cm³) of fibrous cellulose and resins 3 ) 1 / 2The difference in (SP value), that is, the SP of fibrous cellulose MFC value and the SP of the resin POL value, the difference in SP values can be expressed as SP MFC value minus SP POL value. The difference in SP values is preferably from 10 to 0.1, more preferably from 8 to 0.5, and particularly preferably from 5 to 1. If the difference in SP values exceeds 10, the fibrous cellulose may not disperse in the resin, making it impossible to obtain a reinforcing effect. On the other hand, if the difference in SP values is less than 0.1, the fibrous cellulose will dissolve in the resin, fail to function as a filler, and no reinforcing effect can be obtained. In this regard, the SP of the resin (solvent) POL value and the SP of the fibrous cellulose (solute) MFC the smaller the difference in values, the greater the reinforcing effect.

[0094] The solubility parameter (cal / cm 3 ) 1 / 2 (SP value) is a scale representing the intermolecular force acting between a solvent and a solute, and the closer the SP values of a solvent and a solute are, the higher the solubility.

[0095] (Molding treatment) The extrudate of fibrous cellulose and resin from a melt-kneading extruder can be molded into a desired shape. The size, thickness, shape and the like of this molded product are not particularly limited. Similar to general-purpose resins, it can be used as a molding raw material in, for example, sheet form, pellet form, powder form, fibrous form and the like.

[0096] The temperature during the molding treatment is equal to or higher than the glass transition point of the resin, and varies depending on the type of the resin, and is, for example, 90 to 260°C, preferably 100 to 240°C. For the molding treatment of the molding raw material, for example, one or two or more can be selected and used from an injection molding machine, a blow molding machine, a hollow molding machine, a blow molding machine, a compression molding machine, an extrusion molding machine, a vacuum molding machine, a pressure forming machine and the like.

[0097] Furthermore, the extruded material can be spun into fibers and blended with the aforementioned plant materials to form mats or boards. The blending can be done, for example, by simultaneously depositing the materials using an air-lay system.

[0098] (Other compositions) In addition to typical microfiber cellulose, fibrous cellulose may also contain cellulose nanofibers. Cellulose nanofibers are fine fibers, similar to microfiber cellulose, and play a complementary role to microfiber cellulose in improving the strength of the resin. However, if possible, it is preferable to use only microfiber cellulose without including cellulose nanofibers as fine fibers. The average fiber diameter (average fiber width; average diameter of a single fiber) of the cellulose nanofibers is preferably 4 to 100 nm, more preferably 10 to 80 nm.

[0099] Furthermore, fibrous cellulose may contain pulp. The pulp plays a role in significantly improving the dewatering properties of the cellulose fiber slurry. However, as with cellulose nanofibers, it is most preferable not to include pulp, i.e., to have a pulp content of 0% by mass.

[0100] The composite resin composition may also contain, or may contain, fibers derived from plant materials obtained from various plants, including, in addition to fine fibers and pulp, kenaf, jute, Manila hemp, sisal, ganpi, mitsumata, kozo, banana, pineapple, coconut, corn, sugarcane, bagasse, palm, papyrus, reed, esparto, survivalgrass, wheat, rice, bamboo, various coniferous trees (such as cedar and cypress), broad-leaved trees, and cotton.

[0101] The composite resin composition may contain one or more of the following: antistatic agents, flame retardants, antibacterial agents, colorants, radical scavengers, foaming agents, etc., added within a range that does not impair the effects. These raw materials may be added to a dispersion of fibrous cellulose, added during the kneading of fibrous cellulose and resin, added to the resulting mixture, or added by other methods. However, from the standpoint of manufacturing efficiency, it is preferable to add them during the kneading of fibrous cellulose and resin.

[0102] The resin composition may contain an ethylene-α-olefin copolymer elastomer or a styrene-butadiene block copolymer as a rubber component. Examples of α-olefins include butene, isobutene, pentene, hexene, methylpentene, octene, decene, and dodecene.

[0103] The MFR (melt flow rate) of the resin composition (preferably when the fiber content is 55%) is preferably 0.01 to 20 g / 10 min, more preferably 0.02 to 10 g / 10 min, and particularly preferably 0.03 to 5 g / 10 min. If the MFR is 0.01 g / 10 min or higher, extrusion by the extruder can be performed more effectively. However, if the MFR exceeds 1.0 g / 10 min, the molecular weight of the base resin may be reduced too much, and it may not be possible to meet the required strength properties.

[0104] (Definition, measurement method, etc.) (Average fiber diameter) The method for measuring the average fiber diameter of fine fibers (microfiber cellulose and cellulose nanofibers) is as follows: First, 100 ml of an aqueous dispersion of fine fibers with a solid content concentration of 0.01-0.1% by mass is filtered through a Teflon® membrane filter, and the solvent is replaced once with 100 ml of ethanol and three times with 20 ml of t-butanol. Next, the dispersion is freeze-dried and coated with osmium to prepare the sample. This sample is observed using an electron microscope (SEM) at a magnification of 3,000x to 30,000x depending on the width of the constituent fibers. Specifically, two diagonal lines are drawn on the observed image, and three arbitrary straight lines are drawn passing through the intersection of the diagonals. Furthermore, the width of a total of 100 fibers that intersect these three straight lines is measured visually. The median diameter of the measured values ​​is then taken as the average fiber diameter.

[0105] (Aspect ratio) The aspect ratio is the value obtained by dividing the average fiber length by the average fiber width. A larger aspect ratio increases the number of points where snagging occurs, thus increasing the reinforcement effect. On the other hand, it is thought that the ductility of the resin decreases as more snagging occurs.

[0106] (Embodiment of a melt-mixing extrusion apparatus and cooling means) The following describes embodiments of the melt-kneading extrusion apparatus according to the present invention. Figure 1 shows a schematic diagram of a twin-screw fused compounding and extrusion apparatus. This twin-screw fused compounding and extrusion apparatus has a cylindrical main body 10, which is installed extending almost horizontally. The main body 10 is sometimes called a "barrel," and is composed of numerous main body elements connected in the horizontal direction.

[0107] In the main body 10, as shown in Figure 5, a cylinder 10a formed by two overlapping circles is provided, and within it, a double screw shaft 14 is provided, which is rotationally driven around its axis by a rotational driving means 12 such as a motor and a reduction gear (not shown) connected thereto.

[0108] Multiple screw elements 16, primarily for transfer, are connected longitudinally to each screw shaft 14. Various shapes of screw elements 16 can be used. For example, a screw element 16 has the shape shown in Figure 6, has involute flights 16A, and is designed to be transferred towards the extrusion port along the groove 16B between it and the cylinder 10a. The number of flights on a single screw element 16 can be selected as appropriate. In addition, known types of screw elements 16 can be used.

[0109] Along with the screw element, known resistance elements can be used in combination as needed to provide greater material transfer resistance and promote mixing.

[0110] One end of the main body 10 is configured such that a material to be kneaded, such as resin R and the aforementioned fibrous cellulose C, is fed into the cylinder 10a through the input chute 20 and input hole 22.

[0111] In relation to the main body 10, a heating and melting means (not shown) is provided for each main body element, for example, in order to heat the material that has been introduced to the main body 10 to a temperature above the glass transition point of the resin in the material.

[0112] Furthermore, as the material introduced into the main body 10 is heated, and the water in the fibrous cellulose C in particular evaporates, the main body 10 is provided with an appropriate number of vent holes 24 along its longitudinal direction to release the evaporated water and ensure proper melting and mixing. The vent holes 24 are connected to a vacuum pump (not shown), and at appropriate times, the evaporated water is released to the atmosphere through the vent holes 24 via the grooves 16B of the screw element 16 by the vacuum pump. The number of vent holes 24 and vacuum pumps can be selected as appropriate, but it has been found that, for example, it is desirable to provide three sets in the longitudinal direction.

[0113] An extrusion barrel 10C is provided at the tip of the main body 10, and this extrusion barrel 10C has an extrusion opening 10C1 and a communication hole 10C2 that communicates with it. The number and arrangement of the extrusion openings 10C1 and communication holes 10C2 can be selected as appropriate. For example, as shown in Figure 7, they can be formed in an oval shape (a shape in which both ends of a horizontally elongated rectangle are connected in an arc shape).

[0114] The molten and kneaded material discharged from the extrusion port 10C1 is extruded, and a cutting device 30 is provided which has a cutting blade to cut the extruded material. The cutting device 30 of this embodiment is configured to move closer to and further away from the extrusion port 10C1, as shown by the dashed line in Figure 1, for the safety and inspection of the operator. In order to move the cutting blade of the cutting device 30 closer together and further apart, the cutting device 30 is configured to move along a guide (not shown). Alternatively, the plane Tr (see Figure 4) of the rotational trajectory of the cutting blade 40 may be configured to open and close on one side around a vertical axis provided on the left side of Figure 4, for example.

[0115] In the illustrated configuration, the cutting device 30 is housed in a casing 32. The cutting device 30 includes a rotating shaft 34, a swivel plate 36 fixed to the rotating shaft 34, a rotational drive means (e.g., a motor; not shown) for rotating them around their axes, a cutting arm 38 fixed to the swivel plate 36 which rotates clockwise in Figure 4 and extending radially from the axis of rotation (more precisely, along the radial direction at a position offset from the axis of rotation of the rotating shaft 34), and a cutting blade 40 detachably fixed to each of the cutting arms 38. In the illustrated embodiment, four pairs of cutting arms 38 and cutting blades 40 are formed, but the number of pairs is not limited. The number of pairs of cutting arms 38 and cutting blades 40 can be selected according to the desired cutting length of the discharged material, mainly based on the rotational speed around the axis of the swivel plate 36 and the material extrusion speed.

[0116] The molten and kneaded material is extruded from the extrusion port 10C1. The extruded material is cut by the cutting blade 40. To ensure proper cutting, a cooling means 50A is provided that projects cooling water onto the cutting blade 40, which rotates within the plane Tr of the rotational trajectory. A typical example of the cooling means 50 is a cooling water spray nozzle.

[0117] In addition to the cooling means 50A, a blowing means 60 using compressed air, for example, can also be used in combination. Furthermore, the material at the stage of being discharged from the extrusion port 10C1 can be cooled by cooling water from a cooling means 50B, such as a spray nozzle, directed from the extrusion port 10C1 toward the extrusion port 10C1. In this case, the number of cooling means 50A and 50B, the arrangement positions of the cooling means, and the diffusion angle of the spray nozzle can be selected as appropriate. It should be noted that the term "material at the stage of being discharged from the extrusion port" used herein is clearly distinguished from "material at the stage after it has been discharged from the extrusion port, cut, separated, and dropped (for example, the stage after it has been transferred to a cooling and transport mechanism as in Patent Document 1)."

[0118] In addition to the cooling means 50B that projects cooling water onto the material as it is extruded from the extrusion port 10C1, a cooling means 50C is also provided on the substrate of the casing 32 (a plate located in front of the plane of the paper in Figure 4: not shown).

[0119] On the other hand, a pressurized air conduit (not shown) is led to one side of each cutting blade 40, and blowing means 60A to 60D are provided to blow the pressurized air over the cutting edge of the cutting blade 40 to the other side. The blowing means 60A to 60D can be made up of air nozzles connected to a compressor.

[0120] Here, the pivoting trajectory surface Tr around the axis of the rotation axis 34 of the cutting blade 40 covers the extrusion opening 10C1. Although there may be only one extrusion port, it is desirable to form multiple extrusion ports 10C1 as shown in Figure 7 in order to simultaneously obtain material (pellets) with the desired cross-sectional dimensions and cutting length. Even in examples having a large number of extrusion ports 10C1 and two or more cutting blades 40, it is desirable that the rotational trajectory surface Tr of the cutting blade group covers the group of extrusion ports 10C1.

[0121] The above embodiment includes a cooling means 50 (spray nozzles 50A to 50E) that projects cooling water onto the cutting blade 40 and the discharged material when the molten and kneaded material is discharged from the extrusion port 10C1. As described above, even if the discharged material is at a considerably high temperature due to heat accumulation and exhibits stickiness, each cutting blade 40 is cooled by cooling water and does not become hot. Therefore, it is possible to suppress the discharged material or cut chips from sticking to the cutting blade 40, and suitable cutting can be performed. Furthermore, if the system is configured to also project cooling water onto the extruded material or cut chips, the material will be cooled by the cooling water in a short amount of time, which has the advantage of suppressing thermal degradation of the material extruded from the extrusion port of the melt-mixing extruder.

[0122] Furthermore, by providing the blowing means 60A to 60D, even if the extruded material, discharged material, or cut chips attempt to adhere to the cutting blade 40, compressed air is blown out from each of the blowing means 60A to 60D, and the compressed air flies over the cutting edge of the cutting blade 40 to the other side of the cutting blade 40. This suppresses the discharged material or cut chips from adhering to the cutting edge of the cutting blade 40, enabling satisfactory cutting. Furthermore, the compressed air from the blowing means 60A to 60D may be at room temperature or cold air.

[0123] The extruded material is cut into composite resin chips, which are then dropped onto a chute 52 located below the extrusion port 10C1, for example. After being classified as necessary, the composite resin is supplied to its intended use.

[0124] Polypropylene resin can be used as the resin in the embodiment, and the fibrous cellulose can be, for example, microfiber cellulose, preferably with an average fiber diameter of 0.2 to 19 μm. This microfiber cellulose can be obtained based on the explanation described above. Then, a composite material containing, for example, microfiber cellulose with a moisture content of 7% or less and a resin is supplied to a melt-kneading extruder, where the polypropylene resin is heated to a temperature of 160°C or higher, which is its glass transition temperature, melted, and extruded.

[0125] Furthermore, the cutting device and cooling means according to this embodiment can suppress the adhesion (sticking) of the material discharged from the extrusion port of the melt-kneading extruder or the cut chips to the cutting edge of the cutting blade, thereby enabling suitable cutting. [Industrial applicability]

[0126] The present invention relates to a fibrous cellulose composite resin, a method for producing the same, and its use as a resin reinforcing material. For example, the fibrous cellulose composite resin can be used as interior, exterior, and structural materials for transportation equipment such as automobiles, trains, ships, and airplanes; as casings, structural materials, and internal components for electrical appliances such as personal computers, televisions, telephones, and watches; as casings, structural materials, and internal components for mobile communication equipment such as mobile phones; as casings, structural materials, and internal components for portable music players, video players, printing machines, photocopiers, sporting goods, office equipment, toys, and sporting goods; as interior, exterior, and structural materials for buildings and furniture; as office equipment such as stationery; and for other applications such as packaging, trays, protective members, and partition members. [Explanation of Symbols]

[0127] 10...Main body 10C1…Extrusion port 12…Rotational drive means 14... Screw shaft 16... Screw element 18…Materials 30...Cutting means 40...cutting blade 50...Cooling means 50A~50C...Spray nozzle 60A~60D...Blowing method (air nozzle) Tr... Rotation trajectory surface S1, S2... chips

Claims

1. A melt-kneading extrusion step in which a material containing resin and fibrous cellulose is melted and kneaded in a melt-kneading extruder and discharged from an extrusion port, The process includes a cutting step of cutting the molten and kneaded material discharged from the extrusion port with a cutting blade, The cooling step includes projecting cooling water onto at least one of the discharged material and the cutting blade, A melt-kneading extrusion method characterized by the following:

2. The melt-kneading extrusion method according to claim 1, wherein the cooling step has a plurality of cooling water projection nozzles, and at least one projection nozzle projects cooling water onto the discharged material, and at least one projection nozzle projects cooling water onto the cutting blade that performs the cutting step.

3. The melt-kneading extrusion method according to claim 1, wherein the resin is a polypropylene resin, the fibrous cellulose has an average fiber diameter of 0.2 to 19 μm, and the polypropylene resin is heated and melted at a temperature of 160°C or higher.

4. A melt-kneading extruder that melts and kneads a material containing resin and fibrous cellulose and discharges it from an extrusion port, The device includes a cutting blade for cutting the molten and kneaded material discharged from the extrusion port, The cooling means includes a means for projecting cooling water onto at least one of the discharged material and the cutting blade, A melt-kneading extrusion apparatus characterized by the following features.

5. The cutting device comprises a rotating shaft, a rotational driving means for rotating it around its axis, and a cutting arm extending radially from the rotating shaft, having a plurality of cutting blades, and rotating around the axis of the rotating shaft. The pivoting trajectory surface of the cutting blade around the axis of the rotation shaft is in a relationship that covers the extrusion opening. The melt-kneading extrusion apparatus according to claim 4.

6. The melt-kneading extrusion apparatus according to claim 5, having a number of extrusion openings, wherein the swirling trajectory surface of the cutting blade group covers the group of extrusion openings.

7. The melt-kneading extruder according to claim 4, comprising a cylinder, a screw element for melting and kneading the material in the cylinder and transferring it toward the extruder opening, and a means for heating and melting the material.

8. The melt-kneading extrusion apparatus according to claim 4, wherein the cooling means is a plurality of cooling water projection nozzles, and at least one projection nozzle projects cooling water onto the discharged material, and at least one other projection nozzle projects cooling water onto the cutting blade that performs the cutting step.

Citation Information

Patent Citations

  • Resin pellet manufacturing device

    JP2024118213A